Needs analysis of animated video media based on environmental care character in Pancasila education - Rohimah, Rohimah; Chotimah , Umi; Sumarni , Sri (ARKA INSTITUTE, 2025)
Students’ environmental awareness remains relatively low, whereas Pancasila Education holds the potential to integrate environmental care values into learning. This study aimed to analyze the needs for animated video learning media based on environmentally conscious characters in Pancasila Education. A mixed-methods approach was applied, combining quantitative and qualitative data through observations, interviews, and questionnaires with eighth-grade students and teachers. The analysis focused on pedagogical, technical, cognitive, aesthetic, and evaluative aspects to identify the requirements for effective media development. The findings revealed a strong demand for innovative media that integrates environmental values. Students expressed high interest in learning through animated visual content, which they perceived as engaging and easier to understand. Teachers highlighted the relevance of such media to support character education and facilitate abstract Pancasila concepts. The needs analysis thus provides a comprehensive foundation for designing and developing animated video learning media in subsequent research stages. In conclusion, this study indicates the necessity of animated video media that embodies environmental care values in Pancasila Education. The results serve as an essential initial step for future research in developing valid, practical, and effective instructional media.